1999
DOI: 10.1093/bja/83.3.393
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia with i.v. patient-controlled morphine: effect of adding ketamine

Abstract: We have studied the effect of adding ketamine to i.v. morphine patient-controlled analgesia (PCA) for the treatment of pain after laparotomy. Thirty patients were allocated randomly to receive PCA with saline or ketamine in a double-blind, randomized study. Analgesia was started in the recovery room when visual analogue scale (VAS) scores were > 4. A bolus dose of morphine 3 mg was given to all the patients followed by i.v. PCA. Simultaneously, an infusion of ketamine 2.5 micrograms kg-1 min-1 or saline was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(84 citation statements)
references
References 25 publications
6
76
0
2
Order By: Relevance
“…6,18 However, low dose ketamine has less frequent incidence of adverse events and can obviate respiratory depression produced by opioids and produce opioid sparing for postoperative analgesia. 10,19,20 This is consistent with the results of this study. It has been reported that fentanyl can activate N-methyl-Daspartate (NMDA) mediated pain processes, enhancing pain sensitivity, and that this effect is reversed by ketamine pretreatment.…”
Section: Statisticssupporting
confidence: 93%
See 1 more Smart Citation
“…6,18 However, low dose ketamine has less frequent incidence of adverse events and can obviate respiratory depression produced by opioids and produce opioid sparing for postoperative analgesia. 10,19,20 This is consistent with the results of this study. It has been reported that fentanyl can activate N-methyl-Daspartate (NMDA) mediated pain processes, enhancing pain sensitivity, and that this effect is reversed by ketamine pretreatment.…”
Section: Statisticssupporting
confidence: 93%
“…Several drugs, including clonidine, ketamine, magnesium, lidocaine, ketorolac, and steroids have all been shown to be analgesic. [6][7][8][9][10][11] Combining these drugs may potentiate analgesia by separate actions and decrease the risk of side effects by lowering the effective dose for each agent. 12,13 The purpose of this study was to compare fentanyl analgesia with a combination of non-opioid drugs for gastric bypass surgery.…”
mentioning
confidence: 99%
“…Supplementary 18,[20][21][22][25][26][27]29,30,32,34,36,40,41,44,45,50 cardiac or thoracic surgery (six trials), 19,23,35,37,38,53 orthopedic surgery (ten trials), 24,28,31,33,39,43,[47][48][49]51 and other surgery (three trials). 42,46,52 General anesthesia was used in 34 trials; one trial used PCA during and after a uterine artery embolization procedure, 29 and one used either general or regional anesthesia.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The beneficial analgesic efficacy of combined ketamine and morphine administration was reported extensively in literature, In contrast to all previous studies that evaluated the addition of ketamine to PCA morphine for postoperative analgesia [10][11][12], the current study is unique in evaluation of analgesic efficacy of single oral dose of sustained release morphine for patients receiving continuous infusion of sub-anesthetic dose of ketamine. We found that two thirds of morphine group do not need any additional analgesics and expressed significantly lower VAS pain score for 72 h postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…It binds to mureceptors to increase the effectiveness of opioid-induced signalling [9]. Previous studies have found that co-administration of parenteral ketamine and morphine decrease intensity of pain as well as side effects [10,11], however, some studies revealed no benefit [12,13]. The analgesic efficacy of pre-emptive oral morphine and parenteral ketamine infusion is not studied before, so the aim of this study is to assess the analgesic efficacy and tolerability of preoperative single oral dose of sustained release morphine in patients receiving continuous infusion of sub-anesthetic dose of ketamine for patients undergoing MRM.…”
Section: Introductionmentioning
confidence: 99%